Аналіз магнітного кола в генераторі з поперечним магнітним потоком в режимі неробочого ходу - Єгоров, Андрій Володимирович; Маслєнніков, Андрій Михайлович; Дунєв, Олексій Олександрович; Бредун, Руслан Вячеславович (Національний технічний університет "Харківський політехнічний інститут", 2020)
Представлено еквівалентну схему заміщення магнітної системи генератора з поперечним магнітним потоком, який характеризується дисковою конструкцією ротора та збудженням від постійних магнітів, для режиму неробочого ходу. На прикладі ГПП-32-180 подано принцип її рішення з використанням робочої діаграми постійного магніту. Отримана залежність довжини постійного магніту від його намагнічувальної сили на обох радіусах ротора. Дане співвідношення дозволяє правильно вибрати розміри стандартизованих постійних магнітів для збудження генератора. Проведено розрахунок магнітного поля методом скінчених елементів на одному полюсному кроці для підтвердження доцільності методу.

Purpose. The transversal flux generators are very perspective machine type. They can use low wind or water flow to tra nsform their energy into the electricity with good efficiency value. Obtaining the dependence of the length of the permanent magnet on its magnetizing for ce on both radii of the rotor. This ratio allows us to correctly select the dimensions of the standardized permanent magnets to excite the generator. This dependence of permanent magnet length allows us to better analyze the electromagnetic processes in transverse magnetic field generator. Methodology. Analytic and computer calculation of magnetic field of the transversal magnetic flux generator in no-load mode. The analytical methodology must be proved by finite-element method using the 3D simulation in the modern and powerful software such as Ansys Maxwell. It allows us to compare met hodology of TFM design and find the most optimal method for TFM design in accordance with fast and accuracy design process. Results. An equivalent circuit is presented for the magnetic system of the transverse magnetic flux generator, which is characterized by a disk design of the rotor and excitation from permanent magnets in no-load mode. On the example of TFM-32-180, the principle of its solution using the working diagram of a permanent magnet is presented. Originality. The analytical calculation of the correct selection of the standardized permanent magnets dimensions to excite the transversal magnetic flux generator in no-load mode. Practical value. This generators work as a low speed machine and have a rather simple construction. It can be used as high effective machine in low speed rivers or wind turbines installations. Therefore, quality and accurate design process is a practically evaluated. Getting the possibility to analytically design the transversal magnetic flux generator more accurately is a good p ractical value of this perspective type of the machine.
The magnetic circuit analysis of the transverse magnetic flux generator in no-load mode
Keywords: магнітний опір; намагнічувальна сила; проєктування; magnetic resistance; magnetizing force; design